Two adolescent cases of acute tubulointerstitial nephritis after second dose of COVID-19 mRNA vaccine - Jae Hong Choi; Ki-Soo Kang; Kyoung Hee Han (Taylor & Francis Group, 2022)
The Food and Drug Administration (FDA) expanded the emergency use authorization for the BNT162b2 messenger RNA (mRNA) vaccine (Pfizer-BioNTech) for children aged 12-15 years on 10 May 2021. To date, less than a year has passed since vaccination against COVID-19 has been used in children and adolescents, and the overall effects and safety of these vaccines are still being assessed. The BNT162b2 vaccine originally had a favorable profile in 12-17-year-old recipients compared with older ages, and no serious adverse events had previously been reported. Despite various adverse events, the benefit of reducing the infection rate or the frequency of severe COVID-19 has been evaluated to outweigh the harm caused by COVID-19 vaccination. Additionally, several cases of sudden development of new-onset or relapsing glomerular diseases, including acute kidney injury (AKI), have been reported in adults following the BNT162b2 SARS-CoV-2 mRNA vaccine. Herein, we present two cases of adolescents who developed AKI following the second administration of the BNT162b2. These are the first pediatric cases of acute tubulointerstitial nephritis temporarily linked to SARS-CoV-2 vaccination.